Hubungan antara Profil Organisasi Pembelajaran dan Kesediaan Terhadap Perubahan - Zamri, Kamarudin (2009)
The purpose of this study is to determine relationship between learning organization profile and readiness toward change. The study also aims to determine the association between dimensions of learning organization profile i.e. learning dynamics, organization transformation, people empowerment,knowledge management and technology application. A total of 175 respondents involved in this study. Descriptive analysis technique using mean being used to evaluate the level of learning organization profile while ANOVA,Pearson Correlation and regression being used to test the hypothesis. The result shows that the level of learning organization profile and readiness towards change is at neutral and high level. The result also indicates that four learning organization profile dimensions have a significant correlation with readiness toward change. Analysis using regression shows learning organization profile has its own impact towards readiness change in Rejimen Artileri Diraja.